Rapid changes in scores on the two largest principal components of the electroencephalographic spectrum demarcate the boundaries of drowsy sleep. Issue 3 (22nd April 2013) - Putilov, Arcady A; Donskaya, Olga G
Abstract: Neurobiological mechanisms determining a possibility of parsimonious descriptions of the continuous sleep process as a sequence of a few all‐or‐nothing variables called "sleep stages" remain unknown. We tested a suggestion that stage 1 sleep ("drowsy sleep") corresponds to a rapid decay of a wake‐promoting process and that the boundary with stages 2 separates this decay from a rapid buildup of a sleep‐promoting process. The analyzed dataset included power spectra calculated from the electroencephalographic (EEG) records obtained during attempts of 15 adults to stay permanently awake for 43–61 h and during multiple napping attempts of nine sleep‐deprived, nine sleep‐restricted, and 11 sleep‐unrestricted adults. The time courses of scores on the 1st and 2nd principal components of the EEG spectra reflected the suggested phase relationships between rapid changes in the sleep‐ and wake‐promoting processes, respectively. The 1st principal component score was permanently attenuated during wakefulness and stage 1 sleep but started to build up on the boundary with stage 2. In contrast, the 2nd principal component score started to fall down near the wake‐sleep boundary but remained unchanged across stage 2. We concluded that stage 1 sleep corresponds to the decay phase of the wake‐promoting process that precedes the buildup phase of the sleep‐promoting process during stage 2.